DIKSI DALAM KUMPULAN PUISI MANIFESTO KOPLO KARYA ADITYA ARDI N - Siti Maisaroh; Mu'minin; Anton Wahyudi (Jurnal Bastra (Bahasa dan Sastra), 2025)
This research related to diction in poetry collections shows that the author's creativity is very sharp and detailed in using linguistic devices that can beautify the work itself. It is proven by the efforts to empower poetry or rhyme that it is very productive and complex, almost all the poems contained in this poetry collection contain very interesting rhymes so that the aesthetic effect is very well maintained and is able to show the individual characteristics of the author. The beautiful effect in this collection of poetry is apart from the use of various rhyme patterns as well as the way the author displays the number of lines in each stanza. Each stanza in a poem does not always consist of four lines (like most poems) but these vary widely. Apart from the way the rhyme is arranged, the uniqueness of the lines in the poetry verses by the author can be seen from the naming of the title of each poem. The poetry titles are all related to the components that surround the dangdut koplo group community, some are related to the name of the singer, the name of the musician, the guitar, the drummer, the flute, and so on.